Pengaruh Komponen Arus Kas terhadap Harga Saham pada Perusahaan Indeks Liquid 45 (LQ 45) yang Terdaftar pada Bursa Efek Indonesia - Yuridayanti, Nursela; Syahrudin, Syahrudin (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2025)
The capital market plays a crucial role as an investment platform and a source of long-term financing to support national economic growth. One of the leading stock indexes on the Indonesia Stock Exchange (IDX) is the LQ45, which comprises highly liquid stocks with large market capitalizations. In this context, cash flow information becomes a key indicator for investors in evaluating the feasibility of investments. This study aims to analyze the effect of operating cash flow, investing cash flow, and financing cash flow on stock prices of companies listed in the LQ45 index during the 2019–2021 period. A quantitative approach was employed using multiple linear regression analysis on secondary data from 25 purposively selected companies. The simultaneous test results indicate that all three cash flow components significantly influence stock prices. However, the partial test reveals that only investing cash flow has a significant effect (p = 0.017), while operating cash flow (p = 0.328) and financing cash flow (p = 0.423) do not show significant influence. These findings suggest that investors place greater emphasis on long-term growth potential reflected in investing activities rather than operational or financing activities. This study provides valuable implications for corporate management and investors in making strategic decisions based on cash flow information.